Tuberous Sclerosis- A Rare Cause of Seizure - Mondol, Md Badrul Alam; Siddiqui, Md Mahmudur Rahman; Hussain, Md Enayet (Bangladesh Journal of Neuroscience, 2009)
Tuberous sclerosis (TS) is one of the important neurocutaneous syndrome with a variety of clinical manifestations. We present a 19 years old boy with classical triad of Tuberous sclerosis who had seizure, mental retardation, facial angiofibromas and also having other features which cover the newer diagnostic criteria's. TS should be considered as a differential diagnosis in patient of seizure with mental retardation. DOI: http://dx.doi.org/10.3329/bjn.v24i1.3043 Bangladesh Journal of Neuroscience 2008; Vol. 24 (1) : 60-63